Waterborne wood preservatives / Mohd Ezanie Rahmat - Rahmat, Mohd Ezanie (2008)
As we know, timber can be protected from attack by many various insects, fungi, and beetles by applications of wood preservatives. Important factors affecting the quality of treated timber include the care taken in preparing the timber treatment and the preservatives employed. To achieve the best benefit from any preservative type is usually necessary to seal the timber in a suitable force. There are various methods in wood preservative treatment, for example is using water borne preservative ion treated method.